2017
DOI: 10.26226/morressier.58736690d462b8029238401f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical appraisal of international clinical practice guidelines in kidney transplantation using the Appraisal of Guidelines for Research and Education (AGREE) II tool: A systematic review

Abstract: KO, RR, SK, JO, PM and LP were involved in the concept and design of the systematic review. KO and LP designed the search strategy. KO and RR screened search results for relevant full-texts and these were checked by LP. KO and RR performed the data extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…One guideline reached an “average” level of quality, while the remaining two scored a “low” level of quality. Domains in which the highest percentage score was obtained were domain 1 “Scope and purpose” and domain 4 “Clarity of presentation” since aims, target users, and key recommendations were clearly specified in all papers; this is in line with results obtained in previous evaluations, probably because these issues are essential for guideline drafting and therefore properly considered. On the basis of AGREE II items, the quality in these domains could be further improved specifying timing for follow‐up, stratifying recommendations on the basis of clinical features (eg, HPV status), or proposing alternative options for the use of different imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…One guideline reached an “average” level of quality, while the remaining two scored a “low” level of quality. Domains in which the highest percentage score was obtained were domain 1 “Scope and purpose” and domain 4 “Clarity of presentation” since aims, target users, and key recommendations were clearly specified in all papers; this is in line with results obtained in previous evaluations, probably because these issues are essential for guideline drafting and therefore properly considered. On the basis of AGREE II items, the quality in these domains could be further improved specifying timing for follow‐up, stratifying recommendations on the basis of clinical features (eg, HPV status), or proposing alternative options for the use of different imaging techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, CPGs require not only high‐quality theoretical content, but also clinical practicality. Therefore, low scores in ‘applicability’ might waste time and resources, make the clinical outcomes compromised and affect a clinician's confidence 14 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, external review and update procedure are also important. The external reviewers who are outside the working group can make recommendations more reliable, and update procedure can ensure recommendations are valid, reliable and up to date, in case of wasting time and resources 14 . In order to ensure that guidelines are more rigorous, developers need to pay more attention to this part.…”
Section: Discussionmentioning
confidence: 99%
“…Good quality guidelines recommend practice based upon the best available evidence via a robust guideline development process. Recent work has demonstrated that the quality of international guidelines in renal transplantation is variable, with guidelines lacking in robust developmental methodology which may have an impact on their uptake in real clinical practice (18). It is therefore important that clinical decisions do not just rely on guideline-based CDSS, but also take into account local practice and clinical experience as part of the live donor MDT process.…”
Section: Discussionmentioning
confidence: 99%